(untitled) (Journal of the College of Basic Education, 2025)
Industry: Every science that a man practices, whether it is deductive or otherwise, until it becomes like a craft for him, it is called industry. The hadith craftsmanship is the efforts made by the author in the sciences of hadith through his work, and here I spoke about the hadith craftsmanship in the knowledge of hadith according to the teaching sheikh in his interpretation of Mawahib al-Rahman in interpreting the Qur’an, as for the scholar Sheikh Abdul Karim bin Muhammad bin Fattah bin Suleiman bin Mustafa bin Muhammad. Al-Mudarris, known as Sheikh Abdul Karim Bayara, was born to the scholar Sheikh Al-Mudarris in the year: (1323 AH - 1905 AD).This is what the teacher (may God have mercy on him) mentioned, and he knew (Muhammad al-Sufi) for his Sufism and religiosity. The sheikh teacher received Islamic sciences early, to the point that he completed the Holy Qur’an at the age of eight years. He (may God have mercy on him) was ascetic from the world, loyal to his religion, and devoted himself completely. Entirely for the sake of knowledge, teaching, and fatwa, he was the first to compose in the Kurdish language the pulpit sermons of Kurdish preachers. My research consisted of two topics: The first section: The life of Sheikh Abdul Karim Al-Mudarres The second topic: The modern industry in the knowledge of hadith Sources 1- Tafsir Al-Bahr Al-Muhit, by Muhammad bin Yusuf, known as Abu Hayyan (d. 745 AH), studied and edited by Sheikh Adel Ahmed and Sheikh Ali Muhammad, Dar Al-Kutub Al-Ilmiyyah, Beirut, Lebanon. 2- Our Scholars in the Service of Science and Religion, Sheikh Abdul Karim Al-Mudarres (2007 AD), published by: Muhammad Ali Al-Qara Daghi, Iqra Cultural Forum, 1403 AH. 3- Shams Al-Islam Magazine: Issue 30, p. 45, and Risala Al-Ulama’: Issue 9, p. 95 4- - Dictionary of Lisan al-Arab, Muhammad bin Makram bin Ali Abu al-Fadl Jamal al-Din Ibn Manzur al-Ansari, Dar Sader Beirut, third edition 1414 AH. 5- The wish of the disciple in the etiquette of the beneficial and the beneficial, Sheikh Zain al-Din bin Ali al-Amili, known as the second martyr, (911-925 AH), edited by: Reda al-Mukhtari 6- Al-Rahman’s Talents in Interpreting the Qur’an, Abdul Karim Al-Mudarres, Dar for the Revival of Arab Heritage, first edition, 1435 AH - 2014 AD, Beirut, Lebanon, which is the edition approved by the researcher